Doing research in emergency and acute care : making order out of chaos - Guluma, Kama; Wilson, Michael P., 1969-; Hayden, Stephen, 1961- (Chichester, West Sussex, UK ; Hoboken, NJ : John Wiley and Sons, Ltd, 2015)
A practical guide to understanding and navigating the unique challenges faced by physicians and other professionals who wish to undertake research in the ED or other acute care setting. Focusing on the hyper-acute and acute care environment and fulfilling two closely-related needs: 1) the need for even seasoned researchers to understand the specific logistics and issues of doing research in the ED; and 2) the need to educate clinically active physicians in research methodology. This new text is not designed to be a complex, encyclopedic resource, but instead a concise, easy-to-read resource designed to convey key "need-to-know" information within a comprehensive framework. Aimed at the busy brain, either as a sit-down read or as a selectively-read reference guide to fill in knowledge gaps, chapters are short, compartmentalized, and are used strategically throughout the text in order to introduce and frame concepts. This format makes it easy - and even entertaining - for the research novice to integrate and absorb completely new (and typically dry) material. The textbook addresses aspects of feasibility, efficiency, ethics, statistics, safety, logistics, and collaboration in acute research. Overall, it grants access for the seasoned researcher seeking to learn about acute research to empathically integrate learning points into his or her knowledge base. As the ED is the primary setting for hyper-acute and acute care, and therefore a prime site for related clinical trial recruitment and interventions, the book presents specific logistical research challenges that researchers from any discipline, including physicians, research nurse coordinators, study monitors, or industry partners, need to understand in order to succeed.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Medicine -- Research -- Methodology; Emergency medicine; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; Emergency medicine; Medicine -- Research -- Methodology; Medical; Biomedical Research -- methods; Emergency Medicine; Critical Care; Research Design; Electronic books; Electronic books